The Effect of Various Concentrations of the Addition of Emulsifier Tween 80 and Span 80 on the Stability of Cream Formulation Ethanolic Extract of Basil Leaves (Ocimum Americanum L) - Fitria Wulandari; Fauzia Ningrum Syaputri; Nanda Raudhatil Jannah (UNIVERSITAS MUHAMMADIYAH MATARAM, 2022)
ABSTRAKThis study aims to determine the effect of the various concentration of the addition of emulsifier tween 80 and span 80 on the stability of cream preparations containing ethanolic extract of basil leaves (Ocimum americanum L) before and after the freeze-thaw cycling test. The formulation of the cream preparation uses 3 of emulsifier concentrations tween 80 and span 80 (1%, 3%, 5%). The evaluation tests carried out were organoleptic, pH, viscosity, spreadability, adhesion, centrifugal test, emulsion type, homogeneity and freeze-thaw cycling. The results of several tests for the three formulations before and after the freeze-thaw cycling test at temperatures (2-8˚C) and (15-30˚C) for 24 hours, for 3 cycles, such as pH, dispersion, adhesive, and viscosity met the requirements for cream formulation. It has pH 5-5.10, dispersion test 5.1-5.8 cm, adhesiveness test 06.05-06.65 seconds and viscosity test increased significantly with a value range of 2000-30000 cPs. Except, for the centrifugal test of formula 1 because of the separation cream phase. This study concludes that the results of statistical tests analyzed using ANOVA showed no significant difference in the addition of emulsifier tween 80 and span 80 in three variations of cream dosage concentrations before and after freeze-thaw cycling for 3 cycles. Kata kunci : Kemangi; Krim; Emulgator; Span; Tween ABSTRACTPenelitian ini bertujuan untuk mengetahui pengaruh konsentrasi penambahan emulgator tween 80 dan span 80 terhadap stabilitas sediaan krim ekstrak etanol daun kemangi (Ocimum americanum L) sebelum dan sesudah uji freeze-thaw cycling. Formulasi sediaan krim menggunakan 3 konsentrasi emulgator tween 80 dan span 80 yaitu (1%, 3%, 5%). Uji evaluasi yang dilakukan adalah uji organoleptik, pH, viskositas, daya sebar, daya lekat, uji sentrifugal, tipe emulsi, homogenitas dan freeze-thaw cycling. Hasil pengujian ketiga formulasi sebelum dan sesudah uji freeze-thaw cycling pada suhu (2-8˚C) dan (15-30˚C) selama 24 jam 3 siklus seperti pH, daya sebar, daya lekat, dan viskositas memenuhi persyaratan. Hasil untuk Uji pH 5-5,10, uji daya sebar 5,1-5,8 cm, uji daya lekat 06,05-06,65 detik dan uji viskositas yang meningkat signifikan untuk formula 1, 2 dan 3 dengan kisaran nilai 2000-30000 cPs. Kecuali, uji sentrifugal formula 1 terjadi pemisahan fase krim. Penelitian ini menyimpulkan bahwa hasil uji statistik di analisis menggunkan ANOVA menunjukan tidak adanya perbedaan yang bermakna pada penambahan emulgator tween 80 dan span 80 pada tiga konsentrasi sediaan krim sebelum dan sesudah freeze-thaw cycling selama 3 siklus. Keywords : Basil; Cream; Emulsifier; Span; Tween.